Thrown off track? Adjustments of Asian business to shock events - Sierk Horn; Tomoki Sekiguchi; Matthias Weiss (Asian Business & Management, 2021)
The need for a better understanding of radical uncertainty might have never been greater. Ill-preparedness for natural hazards, a resurgence of serious public health concerns or illusions of control over unruly technology question the extent to which we can 'really' shape the world around us. Human-made crises, too, test how we routinely do things. We ask how organisations and actors within them prepare for a collapse of meaning and practise radical uncertainty. Given the breadth and depth of the region's energy (and, as some would argue, turbulences), Asia provides a fitting context for exploring accommodation to and learning from low-probability, high-impact incidents. By reviewing the business and management research on shocks in Asia, we find that there is a strong human side to dealing with the unknown. We argue that what organisations and actors within them do prior, during and after a shock event is substantially contingent upon cultural environments. To elaborate, we discuss the role of the uncertainty avoidance dimension of national culture in dealing with shock events. We further combine this dimension with the universalism-particularism dimension to discuss future research directions. Our exploration of resultant differences in preparedness, resourcefulness and learning offers a more rounded inquiry into how Asian business actors deal with shocks.
Keywords: 650; Shock; Uncertainty; Resilience; Asian business; Cultural differences